O uso de estratégias de Marketing na publicidade de alimentos na televisão e me mídias sociais no Brasil - Jéssica Moreira da Silva (2020)
To analyze the use of marketing strategies by food companies on television (TV) and on social media in Brazil. Methods: Two studies were conducted. The first one was descriptive and included the 18 food companies that most carried advertisements (ads) on Brazilian three open TV channels in April 2018 from 6am to 24am, totalizing 432 hours of record. Subsequently, the posts of these companies on Facebook®, Instagram® and YouTube® were registered. Study 2 was analytic and included all the posts published by Mc Donald’s® on Facebook®, Instagram® and YouTube® during 2019. Both studies investigated the marketing strategies according to the INFORMAS protocol for food marketing monitoring on TV, which refers to the power of the ads, premium offers and brand benefits claims. Double typed data entry was conducted, and data analysis included the description of the frequency of the use of marketing strategies (studies 1 and 2), the comparison of the use of these strategies among the social media platforms and the principal component analysis to describe the profile of marketing identified in each media (study 2). Results: In the study 1, social media published 194 posts and TV runned 52 ads. McDonald’s® stood out for the largest number of ads in the media. Regarding the use of marketing strategies, non-sports celebrities (TV: 13.5%; Facebook®: 19.1%; Instagram®: 30.9%; YouTube®: 31.0%), sporting events (TV: 21.1%; Facebook®: 26.4%; Instagram®: 29.1%; YouTube®: 41.4%) and famous athlete or team (TV: 19.2%; Facebook®: 10.9%; Instagram®: 9.1%; YouTube®: 41.4%) was frequent in all media, besides announcing products with limited editions (TV: 26.9%; Facebook®: 21.8%; Instagram®: 29.1%; YouTube®: 37.9%) and gifts or collectibles (TV: 15.4%; Facebook: 12.7%; Instagram®: 12.7%; YouTube®: 10.3%). Strategies that highlighted sensory characteristics of the products were present on 59.6% of TV ads, 50.9% of Facebook® posts, 29.1% of Instagram® posts and 86.2% of YouTube® videos. Study 2 showed the frequent use of brand benefits claims (Facebook®: 81.3%; Instagram®: 86.4%; YouTube®: 100%) and strategies referred to the power of ads (Facebook®: 43.3%; Instagram®: 39.1%) on Mc Donald’s® posts, especially on YouTube® (66.7%). In addition, three components of marketing strategies were identified in the three social media: ‘childish’, ‘economic’ and ‘celebrities’. On Facebook® and Instagram®, other component was noted and contained strategies related to ‘product’s exaltation’. Conclusion: The monitoring of food advertising showed high use of marketing strategies, with greater diversity of this use on TV and YouTube®